Evaluating the Impact of Conditional Cash Transfer Programs : Lessons from Latin America - Rawlings, Laura B.; Rubio, Gloria M. (World Bank, Washington, DC, 2014)
Unlike most development initiatives, conditional cash transfer programs recently introduced in the Latin America and the Caribbean region have been subject to rigorous evaluations of their effectiveness. These programs provide money to poor families, conditional on certain behavior, usually investments in human capital-such as sending children to school or bringing them to health centers on a regular basis. Rawlings and Rubio review the experience in evaluating the impact of these programs, exploring the application of experimental and quasi-experimental evaluation methods and summarizing results from programs launched in Brazil, Honduras, Jamaica, Mexico, and Nicaragua. Evaluation results from the first generation of programs in Brazil, Mexico, and Nicaragua show that conditional cash transfer programs are effective in promoting human capital accumulation among poor households. There is clear evidence of success in increasing enrollment rates, improving preventive health care, and raising household consumption. Despite this promising evidence, many questions remain unanswered about the impact of conditional cash transfer programs, including those concerning their effectiveness under different country conditions and the sustainability of the welfare impacts.